The Independent Labour Party, 1914-1939 - Laybourn, Keith, author.
1 online resource (xiii, 245 pages).
Keywords: "Historians of political history are fascinated by the rise and fall of political parties and, for twentieth-century Britain, most obviously the rise of the Labour Party and the decline of the Liberal Party. What is often overlooked in this political development is the work of the Independent Labour Party (ILP) which was a formative influence in the growth of the political Labour movement and its leaders in the late nineteenth century and the early to mid-twentieth century. The ILP supplied the Labour Party with some of its leading political figures, such as Ramsay MacDonald, and moved the Labour Party along the road of parliamentary socialism. However, divided over the First World War and challenged by the Labour Party becoming socialist in 1918, it had to face the fact that it was no longer the major parliamentary socialist party in Britain"--